Generation Means Analysis in Cotton (Gossypium hirsutum L.) for Drought Tolerance - Sarwar, Muhammad; Khan, Iftikhar Ahmad; Azhar, Faqir Muhammad; Ali, Asghar (Pakistan Journal of Nutrition, 2012)
Four genotypes of Gossypium hirsutum L; two drought tolerant (NIAB-78, CIM-482) and two susceptible (CIM-446 and FH-1000) were selected to make cross combinations. The parents, F1, F2 and backcross generations of two crosses were studied under drought and normal conditions in the field to find gene action involved in the inheritance of the traits; number of bolls per plant, boll weight, seed cotton yield and ginning out turn. There were significant differences among six generations (P1, P2, F1, F2, BC1 and BC2) of two crosses for all the plant traits both under normal and drought conditions. Generation means analysis revealed additive, dominance and epistatic genetic effects operating in the phenotypic manifestation of the plant characters under both the conditions.